EKSTRAKSI DAN KARAKTERISASI KARAGENAN KASAR RUMPUT LAUT Eucheuma cottoni - Asri jaya; Ni Ketut Sumarni; Ahmad Ridhay (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2019)
Research on extraction and characterization of crude carrageenan from seaweed (eucheuma cottoni) has been carried out. The research aims to determine the optimum extraction time and temperature of crude carrageenan extract from seaweed (eucheuma cottoni). Crude Carrageenan was extracted from seaweed (eucheuma cottoni) by dissolving crushed seaweed in 8% KOH with variation of extraction times are 1 hour, 1.5 hours, 2 hours, 2.5 hours and 3 hours, and temperatures are 50, 70, 90, 110 and 130oC. The results were analyzed using a Completely Randomized Design (CRD). The results show that the optimum extraction time in producing the best quality of crude carrageenan is 2 hours at 50oC with percentage is 78.4%, viscosity is 9.155 cP, sulphate content is 3.102% and gel strength is 7 g. Keywords : eucheuma cottoni seaweed, crude carrageenan, characterization